Oxalis dreyerae (Oxalidaceae), a new species from South Africa - Roets, Francois; Oberlander, Kenneth C. (Phytotaxa, 2016)
Oxalis dreyerae, a new species from the arid Richtersveld region of South Africa, is described. It is most similar to O. inconspicua from which it differs, among others, by having a larger plant body, larger and showier flowers with a broadly trumpet-shaped tube, much larger leaflets, petioles that are thicker than the peduncles, much larger lanceolate sepals and short, stubby teeth on the longer filaments. Its placement within the O. flava clade is supported by nrDNA ITS sequence evidence, which is also consistent with a close relationship to O. inconspicua. Oxalis dreyerae represents the eighth described species of Oxalis endemic to the arid Richtersveld of the Northern Cape, thus supporting the importance of the floristically diverse Gariep Centre of Endemism, of which the region forms a part.